Solve [2x - (7-5x)]/[9x - (3+4x)] = 7/6

Solution:

[2x – (7-5x)]/[9x – (3+4x)] = 7/6

(2x-7+5x)/(9x-3-4x) = 7/6

(7x-7)/(5x-3) = 7/6

Cross multiply

6(7x-7) = 7(5x-3)

=> 42x – 42 = 35x-21

7x = 21

=> x = 21/7 = 3

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question